Bleeding complications after cardiac surgery, before anticoagulation start and then with argatroban or heparin in the early postoperative setting - Klingele, Matthias (J Cardiothorac Surg, 2020)
OBJECTIVES: After elective cardiac surgery a postoperative anticoagulation is obligatory. With critically ill patients the conventional anticoagulation standard heparin is sometimes impossible, e.g. based on HIT II. Then, argatroban is currently a possible alternative, however, due to its impaired metabolism in critically ill patients, anticoagulation effect is harder to anticipate, thus resulting in higher bleeding risk. Furthermore, to date no antidote is available. Hence, severe postoperative bleeding incidents under anticoagulation are commonly mono-causal attributed to the anticoagulation itself. This study concentrates on the number of well-defined postoperative bleeding incidents before any anticoagulation started, then actually under argatroban as well as compared to those under heparin (or switched from heparin to argatroban). MATERIAL AND METHODS: Retrospective study including 215 patients undergoing elective cardiac surgery with a postoperative stay in ICU ≥48 h. Postoperative bleeding complications before and after start of anticoagulation were evaluated. Definition of bleeding complications were: decrease of hemoglobin by more than 2 g/dl without dilution (mean value of volume balance plus one standard deviation) and/or increased need of red blood cell transfusion/day (average transfusion rate + 2 standard deviations). RESULTS: Within the study group of 215 patients, 143 were treated with heparin, 43 with argatroban, 29 switched from heparin to argatroban. Overall, 26.5% (57/215) postoperative bleeding complications occurred. In 54.4% (31/57) bleeding complications occurred before start of anticoagulation; in 43.6% (26/57) after. Of these, 14 bleeding incidents occurred under heparin 9.8% (14/143), 6 under argatroban 14% (6/43) and 6 switched 20.7% (6/29). Higher bleeding complications before start of anticoagulation was related to concomitant factors influencing the overall bleeding risk; e.g. score of severity of illness. These observations further correlate with postoperative, but not anticoagulation induced mortality rate of 2.8% of then given heparin, 20.9% then argatroban, 20.7% then switched. CONCLUSIONS: Postoperative bleeding complications cannot simply be attributed to anticoagulation since occurring often before anticoagulation was started. The risk for bleeding complications after start of anticoagulation was quite comparable for argatroban and heparin. Accordingly, the influence of argatroban on bleeding complications in the postoperative period may be less significant than previously thought.